“Huella de carbono del predio “don Ángel” empresa tabacalera la Francey S.A.” - Cox Intriago, Llandy Layllin (2021)
Carbon footprint is being applied worldwide in different areas, from public and private institutions to companies of different occupations, such as agricultural companies. In this research, the carbon footprint of the tobacco company La Francey S.A., "Don Angel" property, was determined, taking into account part of its production process, from planting to the curing of tobacco leaves and its administrative area such as the warehouse offices. These offices are responsible for managing and providing agrochemicals to the productive sector according to its phytosanitary plan. To determine the carbon footprint, the direct and indirect emissions that the company produces in its activities and processes were classified according to their scope, which is established in the UNE-ISO 14064 standard. Later, the necessary information was collected to determine consumption, such as invoices and electricity bills. Once the information was collected, the emission factors were identified according to each process or activity. The calculation was made by scope, these were added, and a sum was obtained. Finally, the GHG sinks that the company has were taken into account; this value was subtracted from the sum of the scopes, obtaining, as a result, the carbon footprint of the tobacco factory La France and the "Don Angel" property. It was found that the application of agrochemicals is the main source of CO2 being represented by 42.02%. However, within the application of agrochemicals, the excessive use of fertilizers generates more kg of CO2 compared to fungicides and insecticides. Consequently, the second place, 40.48%, is represented by the consumption of LPG; this consumption is reflected in the number of healing houses that exist in the company, which use LPG day and night during the season. Once all the relevant calculations were made, the total carbon footprint was 1802807.97 kg of CO2. Keywords: Carbon Footprint, Emission Factor, Greenhouse Gases, Climate Change.